(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The healthcare systems worldwide are facing challenges that demand increased collaboration between different healthcare professions. As the spectrum of host and patient factors determining successful health care is wide, patients often encounter various reverberations, frequently via multiple health care institutions and worse with incomplete medico-social information exchange than demographic data transfer [r 1]. However, professional boundaries between medicine on the one hand and social and economic professions on the other side pose insurmountable barriers to health care improvement as inpatient health professionals protect their specific attributes and positions against expected encroachment. Due to sector-specific views among professions included in the care of persons with complaints using the same medical (diseases) or physical syndrome (organ failure, dysfunctions) malaise, potential for common care management is often not exhaustively exploited. Product of sector specific professional policies that set the overall satisfaction with intersectoral cooperation in health care rank at 3.25 between 5 (excellent) and ± 9% of social workers and ± 7% of physicians have to propose negative value judgments [r 2] [r 3] [r 4]. Only 27.6%, 26.4%, and 37.8% (social workers, nurses, physicians) notice interdisciplinary work with problems [r 2]. Preferences for professional autonomy would benefit patient care management if integrated and thus coordinated services were possible [r 2]. Nurses are in 28% more often socially involved than physicians, social workers also see their role in signposting health care institutions. On the other hand, physicians more often signpost help outside the health care sector than public health nurses do. In health care settings it is often observed today that there is not an interaction between medicine, care and other professions, so as to form an interdisciplinary, integrated and evolutional perspective. Each profession keeps their expertise in reserve for also far them delineated issues and considerations and passes on to others or even rejects patients in need when approached by other professions. The accepted consequences with regard to the fundamental understanding of medical care as a cross-sectional task often has less in common with the well-being of the patient than with exercises of power, professional dominance and maintenances of the privileges. Assessment of the importance of extraordinary areas of activity (communication and negotiation as well as networking) of health professionals and approximate analyzes for strengthening the high need for multisectoral collaboration in health care settings cannot be found.